Heyne Hard White Wheat - Sears, Rollin G.; Martin, T. Joe; Shroyer, James P. (My University, 1999)
An informational publication about Heyne Hard White Wheat, new, hard white winter wheat variety developed cooperatively by the Kansas Agricultural Experiment Station and the Agriculture Research Service, United States Department of Agriculture.
L918_1999-05
Keywords: L918; Crops; L